GERAKAN BEBAS NYAMUK SEBAGAI UPAYA PENCEGAHAN DAN PENANGGULANGAN DEMAM BERDARAH DI DESA GEDAREN KECAMATAN JATINOM KABUPATEN KLATEN - Istianna Nurhidayati; Faidah Nur; Tifuk Hesti; Erfita edi yati; Sholikhah Nurhidayati; Firdaus Amanu (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Dengue fever in general community distruption caused by problems epidemiological variables, namely environmental, human, and behavior. Empowerment the community for prevention of dengue requires a comprehensive dan integrated comprehensive program in both primary prevention, secondary and tertiary of all element of society. The aim Village build Gedaren to empower communities through the independent in handling dengue. Village build done through in according with the concept of CHN. Elements of the community that is fostered throught the rural communties, health walkers, community and rilegious leaders. Results Village build illustrate able pass the prevention, promotion and protection againt dengue problem. Village build results is expected to the basis of prevention and health promotion program to eradicate communicable diseases in the community trough intensive coaching from health center and Community nureses.Keyword : Dengue Hemorargi fever, prevention, empowerment